Technology management and innovation. Effect on financial business organizations: bibliographical review. - Franklin Renato, Flores Cardenas (2023)
The innovation and technological management are essential in financial organizations. An analysis of user perception was conducted in three branches using an intentional sampling of 300 clients. The majority expressed the need to improve the implementation of technological strategies to provide more timely and efficient service, as well as to develop products and services that better meet their needs. These results underline the importance of innovation and technological management, highlighting areas for improvement to enhance performance and user satisfaction in the financial context.